2018
DOI: 10.1002/lno.10944
|View full text |Cite
|
Sign up to set email alerts
|

Combining nutrient, productivity, and landscape‐based regressions improves predictions of lake nutrients and provides insight into nutrient coupling at macroscales

Abstract: Empirical nutrient models that describe lake nutrient, productivity, and water clarity relationships among lakes play a prominent role in limnology. Landscape‐based regressions are also used to understand macroscale variability of lake nutrients, clarity, and productivity (hereafter referred to as nutrient‐productivity). Predictions from both models are used to inform eutrophication management globally. To date, these two classes of models are generally conducted separately, which ignores the known dependencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…In addition, others have argued that the connections between biogeochemical cycles of different elements make it important to consider multiple nutrients when evaluating the effects of climate on ecosystems (Whitehead & Crossman, ). We found that leveraging information about correlated water quality variables improved precision and accuracy compared to traditional approaches that fail to account for covariance, which is consistent with related studies (Wagner & Schliep, ). Correlations among predictors, responses, and space are often viewed as problems in the data that limit interpretation and must be dealt with prior to analysis, yet we describe a model that uses those characteristics to inform the relationship between climate and lake ecosystems outside the spatial and temporal scope of individual lake data sets.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, others have argued that the connections between biogeochemical cycles of different elements make it important to consider multiple nutrients when evaluating the effects of climate on ecosystems (Whitehead & Crossman, ). We found that leveraging information about correlated water quality variables improved precision and accuracy compared to traditional approaches that fail to account for covariance, which is consistent with related studies (Wagner & Schliep, ). Correlations among predictors, responses, and space are often viewed as problems in the data that limit interpretation and must be dealt with prior to analysis, yet we describe a model that uses those characteristics to inform the relationship between climate and lake ecosystems outside the spatial and temporal scope of individual lake data sets.…”
Section: Discussionsupporting
confidence: 90%
“…Previous work suggests that both precipitation and temperature are mechanistically linked to lake ecosystems (Figure 1), precipitation through the delivery of nutrients from watersheds to lakes (e.g., Arvola et al, 2015;Rose et al, 2017), and temperature by influencing processing rates (e.g., decomposition or primary production) and physical aspects of lakes like stratification (e.g., Kraemer et al, 2015;Kraemer, Chandra, et al, 2017) that can have a strong influence on biology and nutrient cycles. Because different measures of nutrients and productivity are often correlated, modeling them jointly can improve predictions (Wagner & Schliep, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In our inland lakes example we addressed the issue of large-scale predictions to fill in missing data using a joint linear model presented by Wagner and Schliep [13]. With our novel approach for identifying and characterizing extrapolation in a multivariate setting This work results in identification of extrapolated lake locations as well as further understanding of the unique covariate space they occupy.…”
Section: Discussionmentioning
confidence: 99%
“…water quality measurements and variables that describe a lake's ecological context at multiple scales and across multiple dimensions (such as hydrology, geology, land use, and climate). Wagner and Schliep [13] jointly modelled lake nutrient, productivity, and clarity variables and found strong evidence that these nutrient-productivity variables are dependent and that predictive performance was greatly enhanced by explicitly accounting for the multivariate nature of these data. Filstrup et al [1] more closely examined the relationship between Chl a and TP and found that nonlinear models fit the data better than a log-linear model.…”
Section: Predicting Lake Nutrient and Productivity Variablesmentioning
confidence: 99%
See 1 more Smart Citation